2017
DOI: 10.1515/trser-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Mollusc diversity at pulicat Lagoon (India)

Abstract: During our routine ecological survey conducted at Pulicat Lagoon, the most diverse class Gastropods comprised of 26 families with 34 species and Bivalvia with 13 families and 17 species were recorded. The most abundant molluscs species was Crassostrea madrasensis, captured between October 2013 − September 2015. Quite a good number of molluscs were washed ashore. The economic value of the shells in the field of cosmetics was raised high recently. Both in terms of aquaculture and market value the attention shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…Kondisi tersebut membuat area mangrove memiliki kandungan bahan organik tinggi yang dimanfaatkan sebagai sumber makanan berbagai jenis biota. Selain itu, hutan mangrove secara ekologi berperan penting sebagai spawning dan nursery ground (Rangkuti et al, 2017), serta menyediakan habitat (Kordi, 2012) bagi organisme akuatik, seperti ikan (Faruk et al, 2019;Al Jufaili et al, 2021), kerang (Deni et al, 2020;Wulandari et al, 2022;Safitri et al, 2023), udang (Josia et al, 2019;Faisal et al, 2021), kepiting bakau (Yulianti et al, 2018;Kusuma et al, 2021), termasuk beberapa jenis gastropoda.…”
Section: Pendahuluanunclassified
“…Kondisi tersebut membuat area mangrove memiliki kandungan bahan organik tinggi yang dimanfaatkan sebagai sumber makanan berbagai jenis biota. Selain itu, hutan mangrove secara ekologi berperan penting sebagai spawning dan nursery ground (Rangkuti et al, 2017), serta menyediakan habitat (Kordi, 2012) bagi organisme akuatik, seperti ikan (Faruk et al, 2019;Al Jufaili et al, 2021), kerang (Deni et al, 2020;Wulandari et al, 2022;Safitri et al, 2023), udang (Josia et al, 2019;Faisal et al, 2021), kepiting bakau (Yulianti et al, 2018;Kusuma et al, 2021), termasuk beberapa jenis gastropoda.…”
Section: Pendahuluanunclassified
“…During the present research, a considerable difference in the number of fin and shell fishes has been observed with respect to the earlier reports, viz., Raj (2006), who reported 168 species of fishes, 12 species of prawns and 19 species of crabs from the lake, Govindan and Ravichandran ( 2016), who could record 83 finfish species belonging to 14 orders and 50 families from the lake, while, Saraswathy and Pandian (2016) recorded 81 species of fishes, 5 species of prawns and 3 species of crabs, whereas, Ramanibai and Govindan (2018) recorded 51 species of molluscs including gastropods (34) and bivalves ( 17) from the lake. Comparing the data of present research with the literature of Raj ( 2006), it is quite clear that there is visible decline of fish diversity and the same has been witnessed even in the case of molluscan diversity compared to the results of Ramanibai and Govindan (2018).…”
Section: Shellfish Diversitymentioning
confidence: 99%
“…The feeding activity of gastropods produces faeces and mucus which provide suitable habitat for microorganisms (Astor et al, 2015). Thus, the existence of gastropods affects the micro-ecological condition of an ecosystem (Ramanibai and Govindan, 2018). Moreover, the structural composition and abundance of particular species may emphasize the role of gastropod community in the ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, selective capture should be applied to achieve food security. However, gastropods are also utilized for some other purposes, such as medicine, jewellery, tools and pets (Ramanibai and Govindan, 2018). Thus, the potential of gastropod utilization is widely opened and may alter its capture.…”
Section: Introductionmentioning
confidence: 99%